2007
DOI: 10.2174/1874256400701010010
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characteristics, Antimicrobial and Mutagenic Activity in Organically and Conventionally Produced Malus domestica, Annurca

Abstract: Abstract:Total polyphenols content and a partial phenolics composition from pulp and peel of organically and conventionally produced Malus domestica, Annurca were investigated. Furthermore, the antimicrobial effect of these compounds against useful and pathogen microorganism was examined. Finally, their mutagenic activities were evaluated. Organically grown apples showed a greater content of polyphenols, both into the pulp and the peel. The distribution of polyphenols was different between the two types of fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 35 publications
2
10
0
1
Order By: Relevance
“…Our results on the antimicrobial activity confirm that the behavior of an antimicrobial agent can be not only species-specific but also strain-specific [15,16]. The available literature reports several studies ascertaining the antibacterial activity of the essential oil of L. nobilis against different pathogens [6,17,18,19].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results on the antimicrobial activity confirm that the behavior of an antimicrobial agent can be not only species-specific but also strain-specific [15,16]. The available literature reports several studies ascertaining the antibacterial activity of the essential oil of L. nobilis against different pathogens [6,17,18,19].…”
Section: Discussionsupporting
confidence: 79%
“…The inhibition halo test was performed in order to evaluate the potential antimicrobial activity of the L. nobilis essential oil and 1,8-cineole [15]. The Gram-negative Escherichia coli DMS 8579 and Pseudomonas aeruginosa ATCC 50071, and the Gram positive Bacillus cereus DSM 4313, Bacillus cereus 4384 and Staphylococcus aureus DSM 25693 were the bacterial strains tested in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum inhibition zone against P. aeruginosa was observed in case of antibiotic followed by peel extract with mean inhibition zone of 19.00 mm and 13.50mm, respectively and the minimum inhibition was observed in case of pomace extract with mean inhibition zone of 9.05 mm. The results were closely related to the findings of Fratianni et al [31] who observed 6 mm to 13mm inhibitory zone of apple extracts against E. coli. Some other researchers also reported that the apple extract have 11 mm and 6 mm (0.6 cm) inhibition zones against P. aeruginosa [18,20].…”
Section: Evaluation Of Antimicrobial Activity Of Various Extracts Of Applesupporting
confidence: 90%
“…The increasing number of research studies have found that apples can possess some antimicrobial activity. Conventionally produced apples inhibited Bacillus cereus, while the organic peel demonstrated antimicrobial activity against Escherichia coli 0157:07 [47]. It was also reported that the presence of phloretin and its glycosylated derivatives in apples are able to inhibit growth of Gram-positive bacteria, and are active against some strains of the Gram-negative bacteria [48].…”
Section: Growthmentioning
confidence: 99%